Preimage and pseudo collision attacks on round-reduced DHA-256 hash function - Jian ZOU; Wen-ling WU; Shuang WU; Le DONG (Tongxin xuebao)
A preimage attack on DHA-256 hash function reduced to 37-round and a pseudo collision attack on the func-tion reduced to 39-round were proposed respectively.Based on the meet-in-the-middle attack,the Biclique technique was used to improve the preimage attack from 35-round to 37-round.A 39-round pseudo collision was achieved using the Bi-clique technique.Overall,a preimage of DHA-256 was constructed with a complexity of 2255.5and a memory of 23.Besides,a pseudo collision of DHA-256 was proposed with a complexity of 2127.5.These are the best results of preimage and collision attack on DHA-256 hash function.